Cilji implementacije geoinformacijske podpore planiranju in urejanju prostora na lokalni ravni v okviru projekta ONIX - Zakrajšek, Franc (Urbani izziv, 1999)
The project objective is to strengthen the development, establishment, maintenance and use of the geographical data bases in the processes of physical planning and urban management on the local level. It is a part of the Slovenian environmental project Onix. The current state is the phase of implementation.
Keywords: GIS; informacijski sistemi; prostorski informacijski sistemi; prostorsko planiranje; prostorsko urejanje; raba prostora; spatial planning